Proton pump inhibitor leaflets: Is there information on deprescribing? - Marcus Vinícius Lopes Campos; Farah Maria Drumond Chequer; Luanna Gabriella Resende da Silva; André Oliveira Baldoni (Brazilian Journal of Pharmaceutical Sciences)
Abstract This study aims to analyze the existence of information about deprescription in the leaflets of proton pump inhibitor (PPI) medications. The leaflets available on the Brazilian Health Regulatory Agency (ANVISA) and Food and Drug Administration (FDA) websites for the following medications were analyzed: omeprazole, esomeprazole, lansoprazole, dexlansoprazole, pantoprazole, and rabeprazole. The variables collected in each leaflet were the existence: a) about deprescribing; b) of guidance on the deprescription process; c) maximum recommended time for use; and d) risk of prolonged use. This information was analyzed in accordance with the PPI deprescription guideline, from Canada. Regarding the medication leaflets, 83.33 % from ANVISA and 100 % from the FDA did not present explicit and systematic guidance on deprescribing. Regarding the maximum time of use, 100 % of the leaflets from both agencies contained this information. Regarding the risks of prolonged use of the medication, 33.33 % of the ANVISA leaflets and 33.3 % of the FDA leaflets did not report the increased risks described in the guideline. The results highlight a large gap in information about deprescribing in PPI leaflets; this highlighting is necessary to contribute to the promotion of the rational use of medicines.